2022
DOI: 10.18800/psico.202201.020
|View full text |Cite
|
Sign up to set email alerts
|

Critical thinking, creativity, self-efficacy, and teaching practice in Peruvian teacher trainers

Abstract: The relationship between dispositions towards critical thinking, creative-innovative performance, self-efficacy and teaching practice was assessed in Peruvian teacher trainers from the Amazonian region of San Martin. Direct and big relationships were found between all variables. A model that explained 42% of the variance of teaching practice is presented, where dispositions towards critical thinking and creative and innovative performance have a direct effect on teacher self-efficacy. In addition, teacher self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…According to Huerta et al (2022), individuals who are more prone to critical thinking display a stronger creative self-concept and are more open to diversity and challenges. Moreover, critical thinking has a direct effect on creativity and innovation (Saavedra et al, 2022). Additionally, critical thinking has been linked to scientific literacy (Vieira & Tenreiro-Vieira, 2016).…”
Section: Critical Thinkingmentioning
confidence: 99%
“…According to Huerta et al (2022), individuals who are more prone to critical thinking display a stronger creative self-concept and are more open to diversity and challenges. Moreover, critical thinking has a direct effect on creativity and innovation (Saavedra et al, 2022). Additionally, critical thinking has been linked to scientific literacy (Vieira & Tenreiro-Vieira, 2016).…”
Section: Critical Thinkingmentioning
confidence: 99%
“…Self-efficacy, which is a belief in one's own ability to solve issues, is innate in all people. However, people's beliefs about their own abilities to handle problems vary depending on their experiences and personalities [14]. Teachers' creative self-efficacy is defined by social-cognitive theory as the conviction that they can perform tasks to the best of their ability [15].…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy can increase individual confidence and self-confidence to add insight and information in completing work [19]. Related to the teacher's task in the classroom, self-efficacy is very important for every teacher because the success of innovative learning methods is very dependent on the individual teacher's beliefs and self-confidence to apply and develop learning [14], [16] found that selfefficacy positively affects innovative work behavior. Consequently, this investigation leads to the formation of the theory based on the findings of several earlier studies:…”
Section: Introductionmentioning
confidence: 99%
“…This shows that learning in Indonesia is not fully based on curriculum objectives. In addition, the weakness of students in Indonesia is their inability when faced with problems that require higher order thinking skills (Arce-Saavedra, 2022;Astutik, 2020). Higher Order Thinking Skills are important to develop because they include critical and creative thinking, critical thinking is characterized as analytical, focused and objective thinking by optimizing the left brain.…”
Section: Introductionmentioning
confidence: 99%